Optical mapping of biological water in single live cells by stimulated Raman excited fluorescence microscopy - Lixue Shi (Nature Portfolio, 2019)
Recent studies have proposed that intracellular water is different from bulk water at the molecular level. Here the authors introduce a Raman microscopy-based method to image the distribution of water states in living cells, and report intracellular water heterogeneity between nucleus and cytoplasm.